Proceedings of the Thirtieth International Conference on Very Large Data Bases : Toronto, Canada, August 31-September 3, 2004 - Nascimento, Mario A. (Morgan Kaufmann Publishers, 2004)
Proceedings of the 30th Annual International Conference on Very Large Data Bases held in Toronto, Canada on August 31 - September 3 2004. Organized by the VLDB Endowment, VLDB is the premier international conference on database technology.